Sustainable Performance of Village-Owned Enterprises through Social Capital with an Integrated Quality Management Approach - Prasetya, Bangun Putra (Journal of Economics Education and Entrepreneurship, 2024)
The existence of sustainable BUMDes is indispensable to mobilizing the potential of the village and helping poverty alleviation efforts. The purpose of this study is to determine the role of social capital in mediating between integrated quality management and performance sustainability. The approach in this study uses quantitative. The population and sample in this study are BUMDes located in Kulon Progo Regency, D.I. Yogyakarta with a total of 87 BUMDes according to data from the Community Empowerment and Village Empowerment, Population Control and Family Planning Office (DPMKPPKB) of Kulon Progo Regency. The analysis uses SEM. The result of this study is that social capital is able to mediate two variables between Integrated Quality Management and Sustainability Performance